PENDAMPINGAN BRANDING PRODUK MELALUI MEDIA PROMOSI KREATIF DAN DIGITAL PADA KELOMPOK TANI PILANG MAKMUR - Angelini Krisyandi Butar Butar; Erlinda Ophelia Dayanti; Yona Leoni Simatupang; Dwi Laila Maulida; Adi Candra (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The development of agricultural product marketing requires effective branding strategies and the use of digital promotional media to enhance the competitiveness of farmer groups. The Pilang Makmur Farmer Group still faces limitations in managing promotional media, resulting in suboptimal dissemination of product information. This community service activity aims to enhance the capacity of farmer group members in applying digital agripreneurship concepts through mentoring on product branding and the use of creative digital-based promotional media. The methods applied include observation, needs assessment, outreach, training, mentoring, as well as monitoring and evaluation using pre-test and post-test instruments. The outcomes of the activity include the development of a company profile, product catalog, profile video, farmer group leaflets, and educational tourism materials, as well as digital promotional media to strengthen the group’s identity and promote its products. Evaluation results showed an average increase in participants’ understanding from 78.9% on the pre-test to 89.6% on the post-test. These findings indicate that the mentoring activities were able to enhance the knowledge and capacity of farmer group members in implementing branding and digital promotion strategies to support the development of agricultural product marketing. This program also contributes to strengthening the group’s identity and enhancing the competitiveness of its products in a sustainable manner. ABSTRAK Pengembangan pemasaran produk pertanian memerlukan strategi branding dan pemanfaatan media promosi digital yang efektif untuk meningkatkan daya saing kelompok tani. Kelompok Tani Pilang Makmur masih menghadapi keterbatasan dalam pengelolaan media promosi sehingga penyebaran informasi produk belum optimal. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas anggota kelompok tani dalam penerapan konsep digital agripreneur melalui pendampingan penguatan branding produk dan pemanfaatan media promosi kreatif berbasis digital. Metode yang diterapkan meliputi observasi, identifikasi kebutuhan, penyuluhan, pelatihan, pendampingan, serta monitoring dan evaluasi menggunakan instrumen pre-test dan post-test. Luaran kegiatan berupa penyusunan company profile, katalog produk, video profil, leaflet poktan dan eduwisata, serta media promosi digital sebagai sarana penguatan identitas serta promosi produk kelompok tani. Hasil evaluasi menunjukkan peningkatan rata-rata pemahaman peserta dari 78,9% pada pre-test menjadi 89,6% pada post-test. Temuan tersebut menunjukkan bahwa kegiatan pendampingan mampu meningkatkan pengetahuan dan kapasitas anggota kelompok tani dalam mengimplementasikan strategi branding dan promosi digital guna mendukung pengembangan pemasaran produk pertanian. Program ini turut memberikan kontribusi terhadap penguatan identitas kelompok dan peningkatan daya saing produk secara berkelanjutan.